تداخل اللغة الإندونيسية مع اللغة العربية في محادثة الطلاب بمعهد نور الحكيم لومبوك الغربية/Indonesian interference on Arabic in the conversation of the students of Nurul Hakim's Islamic boarding school, West Lombok - M. Syahrul Anwar; Habibia Adama; Bakri Mohammad Bkheet Ahmad; Halimi Zuhdi; Friska Fadhillah (UIN ANTASARI, 2023)
This study aims to study the forms of Indonesian language interferention in Arabic used by students in the madrasah environment who practice their knowledge of Arabic every day and aims to discuss the factors that influence language intervention and the impact of language intervention on students' conversations. This research is qualitative research using descriptive method. The data obtained in this study were through observation and interviews with students and teachers at one of the schools at the Nur Hakim's Islamic boarding school, West Lombok. The results showed that Arabic was used by students at the Nur Hakim's Islamic boarding school, West Lombok. It turns out that they are still very much influenced by their mother tongue, namely Indonesian. These interventions are spread over several aspects such as phonology, morphology, syntax, and lexicography. Teachers try to minimize various forms of language disorders by conducting conversational activities regularly, teaching Arabic grammar and asking students to memorize Arabic vocabulary.